A quantitative analysis of transverse river profiles and its applications for morphotectonics: A case studying Shatt Al-Arab River, Southern Iraq - Al-Mayahi, D.S.B. (Mesopotamian Journal of Marine Sciences, 2022)
The present study discussed the quantitative analysis of Transverse River Profile (TRP) on Shatt Al-Arab channel, by deriving several TRP parameters that can be easily quantifiable and comparable. These parameters are useful to detect the morphotectonic indicators of Shatt Al-Arab basin. Five cross sectional profiles were considered from the previous bathymetrical surveys of Shatt Al-Arab channel starting from Qurna (upstream) at the confluence of Tigris and Euphrates rivers towards Fao (downstream). The results illustrated the main rate of controlling the tectonic activity along the river channel by forming of islands bar at the middle of main river course and increasing in its meanders. The applied analytical technique also efficient in detecting the neotectonic activities for subsurface structures and their effects on deflecting and meanders of the river basin.